2010
DOI: 10.1063/1.3292686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hydrogen and deuterium adsorption on Pd(100)

Abstract: Low energy ion recoil spectroscopy is a powerful technique for the determination of adsorbate position on metal surfaces. In this study, this technique is employed to compare the adsorption sites of hydrogen and deuterium on Pd(100) by detection of either H or D recoil ions produced by Ne(+) bombardment. Comparisons of experimental and Kalypso simulated azimuthal yield distributions show that, at room temperature, both hydrogen isotopes are adsorbed in the fourfold hollow site of Pd(100), however, at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The metal alloy has been an interesting material in medical radionuclide production studies [14][15][16]. The 11-MeV proton beams produced by the cyclotron hit the 50-µm Havar foil, which result in 56 Fe(p,n) 56 Co nuclear reaction as theoretically calculated and experimentally observed in previous studies [17][18][19][20]. Nuclear reactions between the 11-MeV proton beams and the rest of the Havar's individual atoms were not experimentally observed, though they could potentially generate secondary neutrons at low neutron fluxes.…”
Section: Havar Windowmentioning
confidence: 82%
“…The metal alloy has been an interesting material in medical radionuclide production studies [14][15][16]. The 11-MeV proton beams produced by the cyclotron hit the 50-µm Havar foil, which result in 56 Fe(p,n) 56 Co nuclear reaction as theoretically calculated and experimentally observed in previous studies [17][18][19][20]. Nuclear reactions between the 11-MeV proton beams and the rest of the Havar's individual atoms were not experimentally observed, though they could potentially generate secondary neutrons at low neutron fluxes.…”
Section: Havar Windowmentioning
confidence: 82%
“…The behavior of the 11 MeV proton as it passes through the Havar window and in the enriched H2 18 O target was simulated using the Stopping and Range of Ions in Matter (SRIM) 2013 codes (Ziegler et al, 2010), whereas the energy of possible atomic impurities recoiled off the Havar window was examined using both the SRIM 2013 calculated data and the atomic collision equation, which has also been applied in deuterium and hydrogen adsorption studies (Kambali et al, 2008;Gladys et al, 2010;Kambali et al, 2018a;Kambali et al, 2018b;Kambali et al, 2018c). Moreover, collisions between recoiled off cobalt atoms and the silver (Ag) body housing the enriched water target were also simulated to study the origins of the impurities found in the post-irradiated enriched water target.…”
Section: Recoiling and Sputtering Calculationsmentioning
confidence: 99%
“…Fluorine-18 can be produced via 18 O(p,n) 18 F nuclear reaction, in which an enriched water (H2 18 O) target is bombarded by relatively low to medium energy protons (Hjelstuen et al, 2011) in a target system. The target system usually consists of a target body made of silver and a Havar window separating the cyclotron chamber from the target (Kambali et al, 2010;Kambali et al, 2016), although a niobium (Nb)-based window has also been used (Köhler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study 36 has identified that adsorbed hydrogen and deuterium sit at slightly different heights above a Pd(001) surface. In the azimuthal scan (Figure 11), there is a minimum in the yield for scattering of Ne off Pd at 0 (along the [110] azimuth) and at 45 corresponding to the [100] azimuth.…”
Section: Azimuthal Scanmentioning
confidence: 99%